Seismic performance of RC structural squat walls with limited transverse reinforcement - Xiang, Weizheng (2010)
In the last three decades, extensive research works has been conducted to assess the validity of the design provisions of EC8 and ACI 318 for cyclic shear in reinforced concrete (RC) structural walls with low aspect ratios. Significant progress has been achieved in the understanding of global and local responses of such RC structural walls. These squat walls are usually detailed according to current provisions and reinforced against the shear by either conventionally or by adding additional cross-inclined bidiagonal bars to achieve the full ductile behavior of the RC member. Previous research, however, does not provide adequate and conclusive information of structural squat walls with limited transverse reinforcement in boundary columns. Such RC walls may exhibit only limited ductility and the sliding shear mode may dominate. Current research is, therefore, initiated by the need to provide useful and conclusive information related with the local and global responses of squat RC walls with limited transverse reinforcement. In this study, both experimental and numerical investigations of local and global responses of such RC walls under cyclic loadings have been presented in detail. An experimental program has been carried out to explore the local and global responses of a total of eight squat RC structural walls with limited transverse reinforcement. The global and local behavior of these RC walls from the experiments carried out is described in detail. The influence of several design parameters such as axial compression loads, transverse reinforcements in the wall boundary columns and the presence of construction joints at the wall base, on the behavior of such RC walls under cyclic loadings is also reported herein. Reasonable strut-and-tie models for RC structural walls with and without axial loads are then developed to aid in better understanding the force transfer mechanism and contribution of reinforcement in RC walls based on the experiments carried out. Next, an analytical approach, combining the inelastic flexure and shear components of deformation, is proposed to properly evaluate the initial stiffness of tested RC walls.